Analisis Strategi Digital Marketing dalam Meningkatkan Penghimpunan Dana ZIS di Lembaga Dompet Al-Qur’an Indonesia - Mohammad Chilmi Setia Aji; Ahmad Ajib Ridlwan (IAIN Palopo, 2022)
Technological developments require people to adapt to digitalization in their life activities. The rapid development of digital technology in Indonesia can be seen from the number of internet users. In early 2022 internet users in Indonesia reached 204.7 million. The increase in internet users in Indonesia every year is inseparable from the large population in Indonesia. Indonesia as one of the largest Muslim countries in the world has the potential for zakat, infaq, and alms which have the opportunity to increase the economic welfare of the people. Based on data from the ministry of home affairs (kemendagri), the Muslim population in Indonesia was 237.53 million as of December 31, 2021. The large Muslim population in Indonesia and the growing development of digital technology are a challenge for amil zakat institutions in providing information regarding the importance of implementing zakat, infaq, and alms. This study aims to determine the strategies and strength possessed by Dompet Al-Qur'an Indonesia institution in implementing digital marketing to increase ZIS fundraising. This study uses a descriptive qualitative method using primary and secondary data. Primary data was obtained through interviews and secondary data obtained through institutional report data. The results of the study show that Dompet Al-Qur'an Indonesia uses two collection methods, namely conventional and digital. The good relations with donors and beneficiaries that are created in each program are one of the advantages that can give a sense of trust to the institution. The use of digital technology supported by the Social Media Optimalization method in implementing digital marketing also shows innovation and creativity in optimizing the use of media and reaching a broad target donor.